Karakterisasi Bakteri Genus Vibrio Dari Ikan Kerapu (Plectropomus sp.) - Ar Syarif Hidayat (Biogenesis: Jurnal Ilmiah Biologi, 2013)
This research is about the isolation and characterization Vibrio sp. from grouper fish (Plectropomus sp.). This research aimed to observe the amount of vibrio bacteria species based on colony morphology and characterization morphological colony of vibrio isolated from grouper fish(Plectropomus sp.). Bacteria isolation was conducted by isolate some external organs (lesion on its body) and internal organ (jejenum) from grouper fish (Plectropomus sp.). Bacteria was grown on selective medium for vibrio, TCBS (Thiosulfate Citrate Bile Sucrose) agar. The incubation time was 24 hours at 370C. The result showed there are 3 isolate vibrio bacteria that was coded by V1, V2, and V3. V1 morphological characteristis was rounded, edge is entire, convex elevation, green colony colour with blue in the center of colony and smooth tekstur. V2 morphological characteristic was rounded, edge is entire, tortous elevation, colony colour yellow, and smooth tekstur. Morphologicalcharacteristic of V3 was Irregular, egde is Undulate, elevation hill, colony colour yellow and own the smooth tekstur.Keywords: characterization, grouper fish (Plectropomus sp.), isolation, Vibrio